Response of the natural grassland vegetation change to meteorological drought in Xinjiang from 1982 to 2015 - Zhao, Weikang; Jing, Changqing (Frontiers in Environmental Science, 2022)
In recent years, drought frequency has gradually increased, which has reduced vegetation growth and development. The response of grassland to meteorological drought is more sensitive than other vegetation types and can differ substantially among grassland types. In this study, the response of vegetation change to meteorological drought at different time scales was evaluated using data from the normalized difference vegetation index (NDVI) and the standardized precipitation evapotranspiration index (SPEI) to analyze the spatial and temporal variation trends and correlations of the NDVI and SPEI of three grassland types in Xinjiang from 1982 to 2015. Over this 34-year period, the NDVI of meadow, steppe, and desert grassland in Xinjiang increased, with growth rates of 0.002, 0.002, and 0.0003 per decade, respectively, although the increase was insignificant (p > 0.05). The most obvious vegetation improvement areas of the three grassland types were mainly distributed in the Tianshan Mountains. The SPEI-12 of meadow, steppe, and desert grassland in Xinjiang indicated an extremely significant drying trend (p < 0.01), with change rates of −0.31, −0.38, and −0.34 per decade, respectively. The overall pattern was the gradual drying from the northwest to southeast, and the degree of aridification was the largest in eastern Xinjiang. On the annual scale, the correlation between the NDVI and SPEI-12 of the three grassland types was significantly different between northern and southern Xinjiang. The degree to which the vegetation of the three grassland types responded to drought was higher in northern Xinjiang than in southern Xinjiang, and most responses were significant. On the monthly scale, the response of meadow to the SPEI-12 was the highest in autumn (September) (r = 0.53; p < 0.05), the response of steppe to the SPEI-3 was the highest in summer (August) (r = 0.49; p < 0.05), and the response of desert grassland to the SPEI-12 was the highest in summer (June) (r = 0.44; p < 0.05). The results can provide a scientific basis for natural grassland drought response, ecological environmental improvement, and disaster prevention and mitigation.